2015
DOI: 10.5897/jmpr2014.5711
|View full text |Cite
|
Sign up to set email alerts
|

Gas chromatography mass spectrometry (GC-MS) analysis of ethanolic extracts of kolanut (Cola nitida) (vent) and its toxicity studies in rats

Abstract: In this study, gas chromatography-mass spectrometry (GC/MS) was used to analyse the isolated caffeine from kolanut and deternine the acute and chronic toxicity of the extract and the isolated caffeine. In chronic toxicity test, rats were divided into five groups (10 rats per group). Each rat was administered with normal saline (control group), crude kolanut extract (11.9 mg/kg), isolated caffeine (7.5 mg/kg), synthetic caffeine (6 mg/kg) or (6 mg/kg) decaffeinated kolanut extract orally for 90 days. Biochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…The observed decrease was significant ( < 0.05) in test groups against the control (Figure 3). This observation is in line with earlier works of Urgert et al [38] and Fried [39] that reported similar decrease in rats placed on filtered and unfiltered caffeine but not in line with the observation of Salahdeen et al [40]. It has been hypothesized that liver enzymes are a target for caffeine or other components of coffee [37].…”
Section: Resultssupporting
confidence: 82%
“…The observed decrease was significant ( < 0.05) in test groups against the control (Figure 3). This observation is in line with earlier works of Urgert et al [38] and Fried [39] that reported similar decrease in rats placed on filtered and unfiltered caffeine but not in line with the observation of Salahdeen et al [40]. It has been hypothesized that liver enzymes are a target for caffeine or other components of coffee [37].…”
Section: Resultssupporting
confidence: 82%
“…It is hard to predict whether such concentration of Biz-2Fr.3 was achievable in the in vivo studies in the absence of pharmacokinetic data. Nonetheless, the Biz--2 concentrations used in the present study are within the range employed in previous studies to document cellular effects of this natural product (Salahdeen et al, 2015). In summary, the present study identified a bioactive component of bizzy nut that suppresses the growth of androgen--responsive (LNCaP) as well as androgen-independent (DU145) human prostate cancer cells in association with G1 phase cell cycle arrest.…”
Section: Conflict Of Interestsmentioning
confidence: 51%
“…Studies in animals on the effects of chronic (28 days) consumption of Bizzy nut and its active major constituent caffeine have been investigated in mice. These studies report that the chronic consumption of Bizzy nut and caffeine diets caused an apparent toxicity as side effects from a decrease in food intake and body weight and the observed effects are largely due to the high caffeine content (Umoren et al, 2009;Salahdeen et al, 2015;Moradi et al, 2016). Humans have consumed plant phytochemicals for an extensive period and so they are perceived to be reasonably safe.…”
Section: Mechanism Of Anticancer Activitymentioning
confidence: 99%
“…An ethno-medicinal survey carried out by Amujoyegbe and coworkers revealed that the medicinal plant species Cola nitida is traditionally used in Southern Nigeria as medicine for the management of sickle cell disorder (Amujoyegbe et al, 2016). Salahdeen et al (2015) extracted caffeine from kola nuts and used rats as a model system to assess the extract's acute and chronic toxicity in vivo. The results demonstrated that prolonged caffeine administration reduced animal body weight significantly (p < 0.05).…”
Section: An Sicking Ac Vitymentioning
confidence: 99%
“…Among medicinal plants with therapeutic virtues, there are species belonging to the Cola genus (Adewale & Adekunle, 2018;Erukainure et al, 2019). The genus Cola belongs to the family Sterculiaceae (Dah-Nouvlessounon et al, 2015;Salahdeen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%